Penggunaan metode Min-Max dalam pengendalian component material biodiesel pada PT.X - Lubis, Muhammad Fiza (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2023)
Rapid growth in the economy increases industry competition; if planning is done correctly, one of which is stock planning using the min-max stock method, the company's strategy to lower production costs, called efficiency, will occur. The goal of this study is to ascertain whether the min-max stock method is more effective for the examination of biodiesel auxiliary components. The findings showed that there was an excess of inventory for Methanol Auxiliary Materials (CH3OH) of 80.37 percent when only 19.63% was required using the Min-Max method. Specifically, PT. X's initial stock for 2019 was 416,185 kg, while safety stock calculated using the Min-Max method was 317,127.58 kg. In those two years, it was demonstrated that the amount of final inventory of HCl raw materials at PT. X is very large in comparison to inventory calculated using the min-max stock method and that the amount of final inventory of Catalist raw materials (CH3ONa) at PT. X is also very large.